Technical Training Basics, 2nd Edition - Wakefield, Sarah (Association for Talent Development, 2019)
Your essential guide to designing successful training programs. If you're an experienced trainer, training manager, content designer, or curriculum developer, Technical Training Basics will help you tackle the challenges of working with specialized, complex subject matter and in partnership with subject matter experts. Part of ATD's Training Basics series, this complete guide describes the differences between technical and nontechnical training; the principles of gathering information and arranging content for a highly technical course; how to apply specific tools, equipment, and processes in your training; and how to manage your project from designing and developing a pilot course through post-course review. This expanded second edition features new material that focuses on: smaller performance solutions Agile design the learner experience. More exercises, outlines, worksheets, checklists, evaluation forms, and a sample PowerPoint presentation are included to further meet your technical needs.